Odpowiedzi

Najlepsza Odpowiedź!
2010-01-13T17:47:50+01:00
A){x+y=9
{x-y=3

2x = 12
x = 6
6+y=9
y = 3
b){3x+2y=2
{-3x+y=10

3y = 13
y = 4
3x + 8 = 2
x = -2
c){3x+2y=2 / *(-1)
{2x+2y=2

-3x - 2y = -2
2x + 2y = 2

-x = 0

0 + 2y = 2
y = 1
d){x+4y=11 / * (-5)
{2x+5y=10 / * 4

-5x - 20y = -55
8x + 20y = 40

3x = -15
x = -5

-5 + 4y = 11
y = 4


h){9x+8y=1 / * (-5)
{5x-6y=11 / * 9

-45x - 40y = -5
45x - 54y = 99

-99y = 99
y = -1

9x - 8 = 1
x = 1

2010-01-13T17:56:15+01:00
A) x+y=9
x-y=3
x+y+x-y=9+3
2x=12 //2
x=6

x+y=9
6+y=9
y=3

b) 3x+2y=2
-3x+y=10
3x+2y-3x+y=2+10
3y=12 //3
y=4

3x+2y=2
3x+2*4=2
3x=-6 //3
x= -2

c) 3x+2y=2
2x+2y=2 / (-1)

3x+2y=2
-2x-2y=-2
3x+2y-2x-2y=2-2
x=0

2x+2y=2
2*0+2y=2
2y=2 //2
y=1

d)x+4y=11 /(-2)
2x+5y=10

-2x-8y=-22
2x+5y=10
-2x-8y+2x+5y=-22+10
-3y=-12 /(-3)
y=4

x+4y=11
x+4*4=11
x=11-16
x=-5

h) 9x+8y=1 /3
5x-6y=11 /4

27x+24y=3
20x-24y=44
27x+24y+20x-24y=3+44
47x=47 //47
x=1

5x-6y=11
5*1-6y=11
-6y=6 //(-6)
y=-1